2014
DOI: 10.1111/ijn.12337
|View full text |Cite
|
Sign up to set email alerts
|

Profile of atrial fibrillation inpatients: Cardiovascular risk factors and cardiac rehabilitation programme delivery and referral patterns

Abstract: Atrial fibrillation (AF) is increasingly common; however, the cardiovascular risk factor profile and the patterns of delivery and referral to cardiac rehabilitation (CR) in this population are poorly described. We conducted an audit of medical records (n = 145) of patients admitted with AF in one local health district in Sydney, Australia. Patients were aged a mean 72 years, and 51% were male. Lack of risk factor documentation was common. Despite this, 65% had two or more modifiable cardiovascular risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although a 3-month period of PT-X improves physical tness in older patients with permanent AF (7). and it has been shown that older adults require a longer time to retrain physical tness lost after detraining(21), it is rare for patients with AF to have access PT-X (22,23). How to best maintain improvement in physical tness is an active eld of research and development (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although a 3-month period of PT-X improves physical tness in older patients with permanent AF (7). and it has been shown that older adults require a longer time to retrain physical tness lost after detraining(21), it is rare for patients with AF to have access PT-X (22,23). How to best maintain improvement in physical tness is an active eld of research and development (6).…”
Section: Discussionmentioning
confidence: 99%